IR spectra of low-metamorphosed Barzas coal thermally treated in hydrogen medium at various temperatures - Y. Petrov, Ivan; Y. Ushakov, Konstantin; R. Bogomolov, Alexander; G. Tryasunov, Boris (International Journal of Engineering and Technology, 2018)
The processes of coal breakdown into smaller fragments (radicals) taking place in hydrogen medium at high temperatures and pressures represent an important initial stage of the direct coal liquefaction (DCL) technology. In this work, with using a number of analytical techniques (FTIR spectroscopy, elemental, component and chromatographic analyses), the temperature effects (400-550Â°C) on the thermal transformations of low-metamorphosed Barzas coal (sapromixite) in hydrogen medium, have been investigated. Essentially similar extreme temperature dependencies of changes in the alkyl group relative IR intensities and the yields of â€œcoal liquidsâ€ (maltenes and asphaltenes) have been established, with maximal values observed at T = 475Â°C. Also, a close relationship between the yields of gases and H/C atomic ratios for solid products of sapromixite conversions has been discovered.Â Â Â